High-performance reconfigurable computer systems of new generation - Dordopulo, A.I.; Semernikov, E.A.; Kaliaev, I.A.; Levin, I.I. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
The FPGA-based reconfigurable computer systems have high real performance and provide a practically linear growth of performance when the hardware system resource is growing. The paper deals with design features, technical characteristics and values of real performance of computational modules of reconfigurable computer systems designed on the basis of Virtex 5-7 FPGAs. In addition, a software complex intended for the development of parallel applications for the RCS is considered.